Pengaruh Lingkungan Terhadap Transmisi Infeksi Protozoa - Trasia, Reqgi First (Jurnal EnviScience (Environment Science), 2021)
Amebiasis and other protozoal infectious diseases occur worldwide. The highest prevalence is especially in the tropics and subtropics, especially in countries with poor environmental sanitation conditions. In Indonesia, colonic amebiasis is found in endemic conditions with a prevalence of about 18%. Epidemiological research shows that lack of hygiene is a factor that influences the occurrence of infection. In free-living amoeba, the spread can be through fresh water, soil, and feces because this amoeba is thermophilic. The amoeba is commonly found in water contaminated with E.coli. Several other types of protozoa were found to be cosmopolitan, so one form of prevention is by chlorinating drinking water sources using the coagulation-sedimentation-filtration method. In addition, environmental temperature also plays a role in the life cycle of the protozoa. Outside their habitat, protozoa can die at a temperature of 50 C, but can live for 5 days at a temperature of 0 C. Protozoa can also die in culture at a pH of less than 4.9 and cannot live in an aerobic environment. In parasites belonging to sporozoa, oocysts die at a temperature of 45-55 C or when dried and mixed with formalin, ammonia, and iodine solution.